Microbial signature profiles of periodontally healthy and diseased patients - Lourenço, Talita Gomes Baêta; Heller, Débora; Silva-Boghossian, Carina Maciel; Cotton, Sean L.; Paster, Bruce J.; Colombo, Ana Paula Vieira (Journal of clinical periodontology, 2014)
Aim To determine microbial profiles that discriminate periodontal health from different forms of periodontal diseases. Methods Subgingival biofilm was obtained from patients with periodontal health (27), gingivitis (11), chronic periodontitis (35) and aggressive periodontitis (24), and analysed for the presence of >250 species/phylotypes using HOMIM. Microbial differences among groups were examined by Mann–Whitney U‐test. Regression analyses were performed to determine microbial risk indicators of disease. Results Putative and potential new periodontal pathogens were more prevalent in subjects with periodontal diseases than periodontal health. Detection of Porphyromonas endodontalis/Porphyromonas spp. (OR 9.5 [1.2–73.1]) and Tannerella forsythia (OR 38.2 [3.2–450.6]), and absence of Neisseria polysaccharea (OR 0.004 [0–0.15]) and Prevotella denticola (OR 0.014 [0–0.49], p < 0.05) were risk indicators of periodontal disease. Presence of Aggregatibacter actinomycetemcomitans (OR 29.4 [3.4–176.5]), Cardiobacterium hominis (OR 14.9 [2.3–98.7]), Peptostreptococcaceae sp. (OR 35.9 [2.7–483.9]), P. alactolyticus (OR 31.3 [2.1–477.2]), and absence of Fretibacterium spp. (OR 0.024 [0.002–0.357]), Fusobacterium naviforme/Fusobacterium nucleatum ss vincentii (OR 0.015 [0.001–0.223]), Granulicatella adiacens/Granulicatella elegans (OR 0.013 [0.001–0.233], p < 0.05) were associated with aggressive periodontitis. Conclusion There were specific microbial signatures of the subgingival biofilm that were able to distinguish between microbiomes of periodontal health and diseases. Such profiles may be used to establish risk of disease. View the pubcast on this paper at http://www.scivee.tv/journalnode/63057